Pyogenic Pericarditis in Children - Chavarría, Oscar Alberto; Rosa, Folco (Cirugía del Uruguay, 1980)
The patient a 5 - year - old child, suffered from pyogenic pericarditis. Etiopathology, clinics ands treatment of disease are discussed.